A national historical education narrative between myths: from the founder to the racial democracy - Souza, Paulo Crispim Alves de; Fortunato, Ivan (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2019)
This paper aims to develop a debate about the characteristics that consolidated an autonomous national project with imposing pretensions, markedly from the turn of the 19th century to the 20th century. It tries to address how the different myths about equality between people have been treated historically by national education, up to the current document of the National Curricular Common Base. Through the literature review, a historical trajectory is recovered in six stages. It is identified that the myth of "racial democracy" serves as an argument to exclude compensatory measures in the name of a meritocracy that treats dissimilar as similar. Therefore, in addition to recovering the historical silencing, it seeks to indicate means for the construction of a democratic pedagogical political project for the national education system.